Examining Foreign Language Teaching Anxiety in a Saudi University - Alsaedi, Riem; Alamoudi, Khadija (International Journal of English Language Education, 2024)
This study examines the foreign language teaching anxiety (FLTA) faced by EFL teachers in the Saudi context. Moreover, it aimed to investigate the relationship between teachers’ gender and years of experience with their perceived level of FLTA. The study employed a quantitative method and used an adaptive version of FLTAS by Ipek (2006). The participants were 97 EFL teachers working in a Saudi university in Jeddah. The results indicate that the participants experienced a low level of FLTA. The findings also demonstrate a significant relationship between teachers’ level of FLTA and both their gender and years of experience. Male EFL teachers were found to experience more teaching anxiety than female teachers. Furthermore, EFL teachers with more than 10 years of experience faced lower FLTA levels than the other teachers. The findings of this study provide an insight of FLTA in the Saudi context and some recommendations for further research development.